(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This scientific work is devoted to an in-depth analysis of the structural changes in the industrial sector in the sustainable development of the economy of the Khorezm region and the development of a strategy for their improvement. In recent years, in the process of reforms implemented in our country to modernize the economy, ensure interregional equality and diversify the industry, Khorezm region has also achieved significant results in increasing its production capacity, introducing new technologies and expanding the production of export-oriented products.Dedicated to a deep analysis of the structural changes in the industrial sector in the sustainable development of the economy of Khorezm region and the development of a strategy for their improvement. In recent years, in the process of reforms implemented in our country to modernize the economy, ensure interregional equality and diversify the industry, Khorezm region has also achieved significant results in increasing its production capacity, introducing new technologies and expanding the production of export-oriented products.